IDEAL BODY STANDARDS: A MYTH FOR MODERN WOMEN - Riska Mutiah (KOMUNITAS, 2023)
There is no body established outside of history. The body continues to suffer simultaneous redefinition even in the current day. In certain cultures and civilizations, the human body is the site of ideological interpretation. The fashion industry controls ideal body standards through modeling agencies, which have evolved into body training facilities that draw the attention of many young women. Using phenomenological research and Alfred Schutz's theory as an analytical tool, this study investigates body ideals that are myths for modern women. This study finds that the models share a common stock of knowledge when it comes to gazing at the body, which is known as intersubjectivity. Body knowledge is transferred through modeling schools and parents participation. Although the fashion industry's body standards are unclear and lack defined benchmarks, the model assumes that the body training procedure is not a burden but rather a kind of responsibility for their job professionally.